Beneficial Effects of Remifentanil Against Excitotoxic Brain Damage in Newborn Mice - Chollat, Clément; Lecointre, Maryline; Leuillier, Matthieu; Remy-Jouet, Isabelle; Do Rego, Jean-Claude; Abily-Donval, Lénaïg; Ramdani, Yasmina; Richard, Vincent; Compagnon, Patricia; Dureuil, Bertrand; Marret, Stéphane; Gonzalez, Bruno José; et al. (Frontiers in Neurology, 2019)
Background: Remifentanil, a synthetic opioid used for analgesia during cesarean sections, has been shown in ex vivo experiments to exert anti-apoptotic activity on immature mice brains. The present study aimed to characterize the impact of remifentanil on brain lesions using an in vivo model of excitotoxic neonatal brain injury. Methods: Postnatal day 2 (P2) mice received three intraperitoneal injections of remifentanil (500 ng/g over a 10-min period) or saline just before an intracortical injection of ibotenate (10 µg). Cerebral reactive oxygen species (ROS) production, cell death, in situ labeling of cortical caspase activity, astrogliosis, inflammation mediators, and lesion size were determined at various time points after ibotenate injection. Finally, behavioral tests were performed until P18. Results: In the injured neonatal brain, remifentanil significantly decreased ROS production, cortical caspase activity, DNA fragmentation, interleukin-1 levels, and reactive astrogliosis. At P7, the sizes of the ibotenate-induced lesions were significantly reduced by remifentanil treatment. Performance on negative geotaxis (P6-8) and grasping reflex (P10-12) tests was improved in the remifentanil group. At P18, a sex specificity was noticed; remifentanil-treated females spent more time in the open field center than did the controls, suggesting less anxiety in young female mice. Conclusions: In vivo exposure to remifentanil exerts a beneficial effect against excitotoxicity on the developing mouse brain, which is associated with a reduction in the size of ibotenate-induced brain lesion as well as prevention of some behavioral deficits in young mice. The long-term effect of neonatal exposure to remifentanil should be investigated.